The Influence of The Tiktok Application as an Effort to Increase Sales of MSME Actors Causes Consumptive Culture in the Community - Salsabila Mercy Maharani; Luthfia Hayu Widyana; Lailatul Chusnunisa; Ana Nur Ifadah; Procopio B. Dafun Jr (International Journal of Geography, Social, and Multicultural Education, 2024)
The purpose of this study is to determine (1) tiktok, live tiktok, and tiktok shop content as an effort to increase sales of MSME actors; (2) The influence of tiktok shop on people's consumptive behavior; (3) Educational efforts in TikTok content on how to shop wisely; (4) The role of the government in responding to buying and selling activities on the TikTok application. This research uses qualitative methods with data collection techniques through interviews and literature studies sourced from books, journals and research that have been read. The results of this study state that the features provided by TikTok can have a positive impact on MSME players to increase sales and branding. Thus encouraging consumers to shop continuously without seeing the benefits of the item. It is important for the government to ensure that consumers who shop through tiktokshop are protected from harmful business practices